Pengaruh Lingkungan Kerja dan Stres Kerja Terhadap Kinerja Pegawai Melalui Intervening Kepuasan Pegawai Kantor Kecamatan Babelan - Wahyuni, Aulia Dwi; Sawitri, Ni Nyoman; Navanti, Dovina (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to measure the influence of the work environment and work stress on employee performance, mediated by job satisfaction at the Babelan District office. The analysis technique in this research consists of instrument testing. The R-square value of the employee performance variable (Y) is 0.537 and job satisfaction (Z) is 0.745. The f square value of the work environment variable on employee performance is 0.868, which means that the work environment on employee performance has a significant influence, the work environment on job satisfaction is 0.136, which means that the work environment on job satisfaction has a significant influence, job satisfaction on employee performance is 0.002, which means that satisfaction work on employee performance does not have a significant influence, work stress on employee performance of 0.013 means that work stress on employee performance does not have a significant influence, and work stress on job satisfaction of 2.195 means that work stress on satisfaction has a significant influence. Hypothesis test or p value on work environment on job satisfaction (0.000 < 0.05), work stress on job satisfaction (0.000 < 0.050), work environment on employee performance (0.000 < 0.05), work stress on employee performance (0.527 > 0.05), job satisfaction on employee performance (0.835 > 0.05), work environment on employee performance through employee satisfaction (0.786 > 0.05), and work stress on employee performance through employee satisfaction (0.751 > 0.05 )